Modernity and the Challenge of Pluralism: Some Indonesian Lessons - Hefner, Robert W. (Studia Islamika, 1995)
In the tradition of Western social sciences to grow a sense of " hard " about the secularization : the removal of religion from public life ; religion is only a private matter of each person ; he did not have a significant social role .The idea of ​​secularization or the desecration of the Muslim reformer Indonesia has made Islam is not synonymous with social groups - political . Islam has been freed from political conflicts to be accepted by the wider Muslim community . Categories gentry , students , and abangan , Clifford Geertz used to distinguish religious orientation among Javanese Muslims , is no longer relevant to use . Gentry and abangans now been merged into the religious culture of the students . Now taking place what is called a " santrinisasi " or " Islamization " in Indonesia . It takes place in Indonesian society is becoming increasingly modern , where the middle class is getting stronger . Islam has become the culture of the middle class . Modernity hand with Islam . In Indonesia , Islam can also accommodate the challenges of plurality , which is the other side of modernity . Islam has contributed positively to the life of the nation-state of Indonesia.DOI: 10.15408/sdi.v2i4.819